Reason and Its Relationship with Religion According to al-Harits al-Muhasibi - Gumilang, Binangkit; Kaplan, Muhammed Nur (Alhamra Jurnal Studi Islam, 2025)
The researcher began the discussion by discussing al-Muhasibi and his concept of reason and its correlation with religion, followed by examining the sources of knowledge according to al-Muhasibi and his methodology in understanding the text. The researcher explained that reason is essential in Islam because it is an instrument for knowing everything and understanding its meaning. Al-Muhasibi divided the sense of reason into three kinds, namely garīzah (instinct), bayān (explanation), basyīrah (eye of the heart), and ma'rifat (knowing), where the researcher used descriptive and analytical methods to conclude that al-Muhasibi's views had a significant influence in the field of Islamic philosophy that came after al-Muhasibi. The relationship between reason and religion is two things that complement each other, and we cannot separate them. It aims to explain the concept of reason and ensure freedom from ambiguity by using naqli texts for rational meanings. Keywords: Reason; Religion; Relationship; al-Harits al-Muhasibi